PENGARUH LIKUIDITAS, PERTUMBUHAN PERUSAHAAN, KEPUTUSAN INVESTASI, STRUKTUR MODAL, PROFITABILITAS, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN TAMBANG DI BURSA EFEK INDONESIA (BEI) - Lusan Stevani; Karuto; Bayu Wulandari; Muhammad Habibie (Mount Hope Economic Global Journal, 2025)
Firm value is an important performance indicator for stakeholders such as investors, creditors, and management. In the mining sector, factors such as commodity prices, environmental risks, and regulations affect firm value. In Indonesia, the IDX is a place for mining companies to raise capital and provide information to investors. This study uses a quantitative method using a multiple linear regression model, where the number of samples used is 60 samples. The results of this study indicate that liquidity has a significant effect on firm value, firm growth does not have a significant effect on firm value, investment decisions have a significant effect on firm value, capital structure does not have a significant effect on firm value, profitability does not have a significant effect on firm value, leverage has a significant effect on firm value. There is an influence of knowledge Leverage, Investment Decisions, Liquidity, Profitability, Capital Structure, and Firm Growth simultaneously on Firm Value.